Decreased alloreactivity after vaccination against hepatitis B - Ruder, Hans; Kerling, Frank; Daniel, Volker; Korn, Klaus; Waßmuth, Ralf (Transplantation, 1995)
The beneficial effect of blood transfusions on renal allografts disappeared at about the same time when hepatitis B vaccination was introduced in dialysis patients. To determine possible immunosuppressive effects of hepatitis B vaccination, we studied alloreactivity during the course of immunization. Fourteen healthy subjects without serological evidence of hepatitis B were routinely immunized against hepatitis B surface antigen. Plasma and mononuclear cells were isolated and frozen before immunization and after vaccination, respectively. Mean alloreactivity measured by [3H]thymidine uptake decreased from 64,772 cpm before immunization to 40,213 cpm after the third immunization. In crossover experiments, cellular modulation and plasma-dependent modulation of alloreactivity were observed. The immunosuppressive effect of plasma taken 4 weeks after the third vaccination correlated (r=0.9) highly significantly (P<0.005) with the anti-hepatitis B surface antigen antibody titer. Taken together, our data strongly suggest that hepatitis B vaccination is capable of reducing allogenic reactivity.
Gesehen am 22.08.2024